Epoxy adhesive as well as preparation method and application thereof

By introducing a specific proportion of epoxy acrylate resin and alkali metal salts into the epoxy adhesive, the problem of insufficient bonding strength of existing electrically disassembled epoxy adhesives is solved, and high bonding strength and electrically disassembled performance are achieved The combination of the electronic components improves the recovery rate.

CN119463773APending Publication Date: 2025-02-18XIAMEN WELDTONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767992.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing electrically disassembleable epoxy adhesive has low bonding strength, which limits its promotion and use in electronic products.

Method used

By introducing a specific proportion of epoxy acrylate resin and alkali metal salts into the epoxy adhesive, it is given the electrically disassembleable properties under power-on conditions while improving the bonding strength.

Benefits of technology

It realizes that epoxy adhesives have electrically disassembleable properties while maintaining high bonding strength, improving the recovery rate of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169485710000131
    Figure BDA0005169485710000131
Patent Text Reader

Abstract

The invention belongs to the technical field of epoxy adhesives, and particularly relates to an epoxy adhesive as well as a preparation method and application thereof. The epoxy adhesive contains epoxy resin, epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, toner, inorganic filler and auxiliaries, and the mass ratio of the epoxy resin to the epoxy acrylate resin to the alkali metal salt is 100: (20-150): (20-200). The epoxy acrylate resin and the alkali metal salt in a specific proportion are introduced into the epoxy adhesive, so that the prepared epoxy adhesive has excellent bonding performance and electrically detachable performance, and has a wide practical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy adhesives, and in particular relates to an epoxy adhesive and a preparation method and application thereof. Background Art

[0002] Epoxy adhesives mainly contain epoxy resin and curing agent. In addition to epoxy resin and curing agent, they may also contain auxiliary materials such as toughening agent, diluent, accelerator, coupling agent, etc. Epoxy adhesives are well-known in electronic products for their excellent bonding performance and versatility, and are known as "all-purpose glue" or "strong glue".

[0003] With the global requirements for environmental protection and energy conservation, many important electronic components need to disassemble some of the bonded parts for reassembly, repair and recycling in the actual production process. These applications usually require the adhesive to have detachable properties while maintaining a certain bonding strength. However, due to the strong bonding performance of epoxy adhesives, the surfaces of these used electronic components are attached with residual adhesives, which cannot be recycled, thus causing serious waste. In recent years, there is a technology that adds alkali metal salts and solvated matrix to epoxy adhesives to form liquid electrolytes, thereby giving epoxy adhesives the function of being disassembled under power-on conditions, thereby achieving gentle disassembly without damaging the electronic bonding substrate. However, although the existing power-on disassembleable epoxy adhesives have the function of being disassembled under power-on conditions, their bonding strength is still far behind that of traditional widely used epoxy adhesives, which limits the promotion and use of such electrical disassembly epoxy adhesives. Summary of the invention

[0004] The first object of the present invention is to provide an electrically dismantling epoxy adhesive with high bonding strength in view of the disadvantage of poor bonding strength of the electrically dismantling epoxy adhesive in the prior art.

[0005] The second object of the present invention is to provide a method for preparing the above-mentioned epoxy adhesive.

[0006] The third object of the present invention is to provide application of the above epoxy adhesive in bonding electronic products.

[0007] The epoxy adhesive provided by the invention contains epoxy resin, epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, color powder, inorganic filler and auxiliary agent, wherein the mass ratio of the epoxy resin, epoxy acrylate resin and alkali metal salt is 100:(20-150):(20-200).

[0008] The preparation method of the epoxy adhesive provided by the invention comprises the steps of uniformly mixing epoxy resin, epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, color powder, inorganic filler and auxiliary agent to obtain the epoxy adhesive.

[0009] Existing electrically dismantling epoxy adhesives usually adopt the method of introducing alkali metal salts and solvated matrices to form liquid electrolytes, thereby giving them the ability to be electrically dismantled. However, since the liquid electrolyte cannot undergo a curing reaction during the curing process of the adhesive, it will exist in the adhesive system in the form of a "plasticizer" after the adhesive is cured. This "plasticizer" will affect the internal structure of the cured colloid and have a negative impact on the bonding strength of the adhesive, causing a significant decrease in the bonding strength. Therefore, how to solve the problem of the presence of "plasticizers" in the cured colloid is the key to improving the bonding performance of electrically dismantling epoxy adhesives.

[0010] The key to the present invention is that by introducing a specific proportion of epoxy acrylate resin and alkali metal salt into the epoxy adhesive, on the one hand, the introduced epoxy acrylate resin can make the alkali metal salt uniformly dissolve and disperse in the epoxy adhesive body, giving it the performance of being electrically disassembled under power-on conditions; on the other hand, the epoxy acrylate resin can undergo a curing reaction together with the epoxy resin. Compared with the difficult-to-curing solvated matrix commonly used in the prior art, it can solve the negative impact of the "plasticizer" formed by the uncured solvated matrix on the bonding performance of the epoxy adhesive. In addition, the ionic conductivity of the acrylate monomer decreases less after curing than when it is not cured, and has little effect on the ion migration ability of the cured system. It is speculated that this may be because in addition to being affected by the action of the solvated matrix, ion migration is also related to the dipole interaction between the dissociated ions and the polymer segments. The movement of the polymer segments can help ion migration. Therefore, the epoxy acrylate resin can still maintain good electrical disassembly performance after curing.

[0011] In summary, the present invention introduces a specific ratio of liquid epoxy acrylate resin and alkali metal salt into the epoxy adhesive, so that the epoxy adhesive prepared thereby has both excellent bonding performance and electrical disassembly performance, and has broad practical application prospects. DETAILED DESCRIPTION

[0012] The epoxy adhesive provided by the present invention contains epoxy resin, epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, color powder, inorganic filler and auxiliary agent. The epoxy adhesive provided by the present invention obtains the effect of electrical disassembly by adding alkali metal salt on the one hand, and makes the whole adhesive system have better compatibility and improves the bonding strength by adding epoxy acrylate to dissolve alkali metal salt on the other hand, that is, by introducing epoxy acrylate and alkali metal salt into the epoxy adhesive system, the epoxy adhesive is given good bonding performance, and the obtained epoxy adhesive can be peeled off from the bonding interface under the condition of voltage application, so as to achieve the effect of electrical disassembly and improve the recovery rate of electronic components. Wherein, the mass ratio of the epoxy resin, epoxy acrylate resin and alkali metal salt is 100: (20-150): (20-200). Based on 100 parts by weight of the epoxy resin, the content of the epoxy acrylate resin is 20 to 150 parts by weight, such as 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 parts by weight or any value therebetween; the content of the alkali metal salt is 20 to 200 parts by weight, such as 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 parts by weight or any value therebetween. The mass ratio of the curing agent to the epoxy resin can be (20-200):100, such as 20:100, 30:100, 40:100, 50:100, 60:100, 70:100, 80:100, 90:100, 100:100, 110:100, 120:100, 130:100, 140:100, 150:100, 160:100, 170:100, 180:100, 190:100, 200:100 or any value therebetween. The mass ratio of the coupling agent to the epoxy resin may be (0.4-50):100, such as 0.4:100, 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100 or any value therebetween. The mass ratio of the toner to the epoxy resin may be (0.4-50):100, such as 0.4:100, 1:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100, 50:100 or any value therebetween.The mass ratio of the inorganic filler to the epoxy resin can be (120-600):100, such as 120:100, 150:100, 200:100, 250:100, 300:100, 350:100, 400:100, 450:100, 500:100, 550:100, 600:100 or any value therebetween. The mass ratio of the auxiliary agent to the epoxy resin can be (0-200):100, such as 0, 5:100, 10:100, 20:100, 40:100, 60:100, 80:100, 100:100, 120:100, 140:100, 160:100, 180:100, 200:100 or any value therebetween.

[0013] In a preferred embodiment, the content of the epoxy resin is 10 to 25 parts by weight, such as 10, 12, 15, 18, 20, 22, 25 parts by weight or any value therebetween; the content of the epoxy acrylate resin is 5 to 15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the alkali metal salt is preferably 5 to 20 parts by weight, such as 5, 8, 10, 12, 15, 18, 20 parts by weight or any value therebetween; the content of the curing agent is 5 to 20 parts by weight, such as 5, 8, 10, 12, 15, 18, 20 parts by weight or any value therebetween; the content of the coupling agent is 0 .1 to 5 parts by weight, such as 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween; the content of the color powder is 0.1 to 5 parts by weight, such as 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 parts by weight or any value therebetween; the content of the inorganic filler is 30 to 60 parts by weight, such as 30, 35, 40, 45, 50, 55, 60 parts by weight or any value therebetween; the content of the auxiliary agent is 0 to 20 parts by weight, such as 0, 2, 5, 8, 10, 12, 15, 18, 20 parts by weight or any value therebetween.

[0014] In the present invention, the epoxy resin may be an aliphatic epoxy resin having two or more epoxy groups, or an aromatic epoxy resin having two or more epoxy groups, or a mixture of the two. The aliphatic epoxy resin having two or more epoxy groups may be at least one of an alicyclic epoxy resin, a glycidylamine epoxy resin, a hydantoin epoxy resin, an epoxy resin having a siloxane skeleton, and the like. Specific examples of the alicyclic epoxy resin include, but are not limited to, vinyl (3,4-cyclohexene) dioxide and / or 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-dioxane. The glycidylamine epoxy resin may be, for example, tetraglycidylbis(aminomethyl)cyclohexane. The hydantoin epoxy resin may be, for example, 1,3-diglycidyl-5-methyl-5-ethylhydantoin. The epoxy resin having a siloxane skeleton may be, for example, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane. The aromatic epoxy resin having more than two epoxy groups can be various existing epoxy resins with two epoxy groups and containing aromatic ring structures, and specific examples thereof include but are not limited to: at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, tetrabromobisphenol A epoxy resin, fluorene epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin, biphenyl epoxy resin, glycidylamine epoxy resin, naphthalene ring-containing epoxy resin, etc., and specifically at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, o-hydroxymethyl bisphenol A diglycidyl ether, dihydroxymethyl bisphenol A diglycidyl ether, tetrabromobisphenol A diglycidyl ether, resorcinol diglycidyl ether, pyrogallol triglycidyl ether pentaerythritol diglycidyl ether. If the epoxy resin is in a crystalline state, it is necessary to heat the epoxy resin to a non-crystalline state before use.

[0015] The present invention has no particular limitation on the type of epoxy acrylate resin, and can be any existing compound obtained by ring-opening esterification reaction of epoxy resin and acrylic acid, including unmodified epoxy acrylate resin and / or modified epoxy acrylate resin, and specifically at least one of 2-hydroxy-3-phenoxypropyl acrylate, bisphenol A epoxy acrylate, fatty acid epoxy acrylate, phenolic epoxy acrylate, epoxy soybean oil acrylate and epoxy diacrylate can be cited. In addition, the viscosity of the epoxy acrylate resin at 25° C. is preferably 500 to 20000 mPa.s, such as 500, 800, 1000, 2000, 5000, 8000, 10000, 12000, 15000, 18000, 20000 mPa.s or any value therebetween. Preferably, the epoxy acrylate resin is in liquid state at room temperature. When the viscosity of the epoxy acrylate resin is controlled within the above preferred range, it is more conducive to uniformly dispersing the alkali metal salt in the epoxy adhesive system, thereby giving the system better electrical disassembly performance.

[0016] In the present invention, the alkali metal salt may be a compound composed of an alkali metal cation and at least one anion of an organic acid anion, an inorganic acid anion, and an organic sulfonyl imide anion, preferably a fluorine-containing alkali metal lithium salt. The inventors of the present invention have found that when the alkali metal salt is preferably a fluorine-containing alkali metal lithium salt, it can impart better electrical disassembly performance to the epoxy adhesive. Specifically, the alkali metal cation of the alkali metal salt may be at least one of lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs), preferably at least one of lithium (Li), sodium (Na) and potassium (K). The anion of the alkali metal salt can be at least one of trifluoromethanesulfonate ion, carboxylate ion, sulfinate ion, chloride ion, sulfate ion, sulfite ion, tetrafluoroborate ion, hexafluorophosphate ion, hexafluoroantimonate ion, nitrate ion, and bistrifluoromethanesulfonyl imide ion, preferably trifluoromethanesulfonate ion, tetrafluoroborate ion, hexafluorophosphate ion, hexafluoroantimonate ion, and bistrifluoromethanesulfonyl imide ion. Specific examples of the alkali metal salt include, but are not limited to, at least one of sodium acrylate, potassium acrylate, sodium methacrylate, potassium methacrylate, lithium chloride, sodium chloride, potassium chloride, lithium acetate, sodium acetate, potassium acetate, lithium carbonate, sodium carbonate, potassium carbonate, lithium sulfate, sodium sulfate, potassium sulfate, lithium nitrate, sodium nitrate, potassium nitrate, lithium tetrafluoroborate, sodium tetrafluoroborate, potassium tetrafluoroborate, lithium hexafluorophosphate, sodium hexafluorophosphate, potassium hexafluorophosphate, lithium hexafluoroantimonate, sodium hexafluoroantimonate, potassium hexafluoroantimonate, lithium trifluoromethanesulfonate, sodium trifluoromethanesulfonate, potassium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonimide, sodium bistrifluoromethanesulfonimide, and potassium bistrifluoromethanesulfonimide.

[0017] In the present invention, the type and source of the curing agent can be various existing options, for example, it can be selected from at least one of amine curing agents, acid anhydride curing agents and imidazole curing agents. The amine curing agent can be listed as at least one of aliphatic polyamines, alicyclic polyamines, piperazine-type polyamines and aromatic polyamines. Among them, the aliphatic polyamine can be listed as at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, triethanolamine, dicyandiamide, triethylenetetramine, tetraethylenepentamine, meta-xylylenediamine, trimethylhexamethylenediamine, and 2-methylpentamethylenediamine. The alicyclic polyamine can be listed as at least one of isophoronediamine, 1,3-bisaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornenediamine, and 1,2-diaminocyclohexane. The piperazine-type polyamine can be listed as N-aminoethylpiperazine and / or 1,4-bis(2-amino-2-methylpropyl)piperazine. The aromatic polyamines include at least one of diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-diamino-3,3'-diethyldiphenylmethane, bis(methylthio)toluenediamine, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenylsulfone, diethyltoluenediamine, trimethylenebis(4-aminobenzoate) and polytetramethylene oxide-diparaaminobenzoate. The anhydride curing agent includes at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, endomethyltetrahydrophthalic anhydride, alkenyl-substituted succinic anhydride, methylnadic anhydride and glutaric anhydride. Examples of the imidazole curing agent include 2-substituted imidazole compounds such as imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, and trimellitic acid imidazole salts such as 1-cyanoethyl-2-undecylimidazole. , at least one of triazine adducts such as 4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-dihydroxymethylimidazole.In addition, the optimal ratio of the curing agent is 0.6 to 1.3 equivalents relative to the epoxy equivalent of the epoxy resin.

[0018] In the present invention, the type and source of the coupling agent can be various existing options, and can be selected from at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanatesilane, and its specific examples include but are not limited to: γ-aminopropyl triethylsiloxane, γ-glycidoxypropyl trimethoxysiloxane, γ-methacrylate propyl trimethoxysiloxane, γ-mercaptopropyl trimethoxysiloxane, vinyl tri-tert-butyl peroxide silane, β-hydroxyethyl-γ-aminopropyl triethoxysiloxane, aniline methyl triethoxysilane and diethylene triaminopropyl triethoxysilane. The addition of the coupling agent helps to promote the uniform dispersion of the solid electrolyte in the epoxy adhesive system, thereby facilitating the realization of the electrical disassembly performance of the epoxy adhesive system.

[0019] In the present invention, the color powder can be any existing substance that can impart color to the epoxy adhesive without affecting its performance, and can be specifically selected from at least one of carbon black, iron oxide color powder, chromate color powder, cadmium color powder, ultramarine and phthalocyanine blue. Among them, the iron oxide color powder can be at least one of iron yellow, iron red and iron black. The chromate color powder can be chrome yellow and / or chrome green. The cadmium color powder can be cadmium red and / or cadmium yellow.

[0020] In the present invention, the inorganic filler can be any existing material that can improve the heat resistance, moisture resistance, electrical conductivity, thermal conductivity and other properties of the epoxy adhesive, and can specifically include at least one of calcium carbonate, dolomite powder, calcite, quartz powder, kaolin powder, calcined kaolin powder, talcum powder, mica powder, feldspar powder, wollastonite powder, silica powder, sepiolite powder and glass powder. The average particle size of the inorganic filler is preferably 0.1 to 10 μm, such as 0.1 μm, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any value therebetween. In addition, the surface of the inorganic filler is preferably treated with a silane coupling agent, which can improve the compatibility of the inorganic filler with the epoxy adhesive system, and is more conducive to the improvement of the various properties of the epoxy adhesive. The specific treatment method can be any existing conventional selection, which can be known to those skilled in the art and will not be repeated here.

[0021] In the present invention, the type of the auxiliary agent is not particularly limited, and for example, the auxiliary agent may be selected from at least one of a defoaming agent, a leveling agent, a dispersant, and an antioxidant.

[0022] The preparation method of the epoxy adhesive provided by the present invention comprises mixing epoxy resin, epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, color powder, inorganic filler and auxiliary agent uniformly to obtain epoxy adhesive. In a preferred embodiment, the mixing method specifically comprises the following steps: mixing epoxy resin, liquid epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, color powder and auxiliary agent uniformly by scraping the wall in a container, adding inorganic filler to the obtained mixture and continuing to scrape the wall to mix uniformly, passing the obtained mixture through three rollers twice, and then transferring it to a double planetary hybrid power stirring kettle for stirring and mixing, and then vacuuming and degassing the obtained mixture, and sealing and storing it for standby use after discharging.

[0023] The invention also provides application of the epoxy adhesive in bonding electronic products.

[0024] The present invention will be described in detail below by way of examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0025] In the following embodiments and comparative examples, the raw materials and sources of epoxy resin are as follows: bisphenol F diglycidyl ether, purchased from Mitsubishi Chemical Corporation, brand 806, epoxy equivalent of 160g / eq; bisphenol A diglycidyl ether, purchased from Mitsubishi Chemical Corporation, brand 828, epoxy equivalent of 184g / eq; bisphenol S diglycidyl ether, purchased from Wuhan KMK Biopharmaceuticals, brand KMK-869.

[0026] In the following examples and comparative examples, the raw materials and sources of epoxy acrylate resins are as follows: bisphenol A epoxy acrylate, purchased from Changxing Materials Industry Co., Ltd., brand 623-100, liquid; fatty acid epoxy acrylate, purchased from Changxing Materials Industry Co., Ltd., brand 622-100, liquid; phenolic epoxy acrylate, purchased from Changxing Materials Industry Co., Ltd., brand 625C-45, liquid; epoxy soybean oil acrylate, purchased from Changxing Science and Technology Industry Co., Ltd., brand 6265, liquid.

[0027] Example 1

[0028] S1. 10 parts by mass of 2-hydroxy-3-phenoxypropyl propyl acrylate and 5 parts by mass of sodium methacrylate were scraped and mixed in a container to obtain a premix;

[0029] S2. 25 parts by mass of bisphenol F diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0030] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0031] Example 2

[0032] S1. 15 parts by mass of bisphenol A epoxy acrylate and 5 parts by mass of lithium bis(trifluoromethanesulfonyl)imide were scraped and mixed in a container to obtain a premix;

[0033] S2. 20 parts by mass of bisphenol F diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the above premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0034] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0035] Example 3

[0036] S1. 5 parts by mass of fatty acid epoxy acrylate and 5 parts by mass of sodium acrylate were scraped and mixed in a container to obtain a premix;

[0037] S2. 25 parts by mass of bisphenol F diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0038] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0039] Example 4

[0040] S1. 10 parts by mass of novolac epoxy acrylate and 5 parts by mass of lithium tetrafluoroborate were scraped and mixed in a container to obtain a premix;

[0041] S2. 25 parts by mass of bisphenol S diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the above premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0042] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0043] Example 5

[0044] S1. 10 parts by mass of 2-hydroxy-3-phenoxypropyl propyl acrylate and 10 parts by mass of sodium hexafluorophosphate were scraped and mixed in a container to obtain a premix;

[0045] S2. 20 parts by mass of bisphenol F diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the above premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0046] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0047] Example 6

[0048] S1. 15 parts by mass of 2-hydroxy-3-phenoxypropyl propyl acrylate and 5 parts by mass of sodium hexafluoroantimonate were scraped and mixed in a container to obtain a premix;

[0049] S2. 10 parts by mass of bisphenol F diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the above premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0050] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0051] Example 7

[0052] S1. 10 parts by mass of 2-hydroxy-3-phenoxypropyl propyl acrylate and 5 parts by mass of sodium trifluoromethanesulfonate were scraped and mixed in a container to obtain a premix;

[0053] S2. 25 parts by mass of bisphenol S diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the above premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0054] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0055] Comparative Example 1

[0056] An epoxy adhesive was prepared according to the method of Example 1, except that sodium methacrylate was not added. The other conditions were the same as those of Example 1 to obtain an epoxy adhesive.

[0057] Comparative Example 2

[0058] An epoxy adhesive was prepared according to the method of Example 1, except that the amount of sodium methacrylate was reduced to 1 part by mass, and the other conditions were the same as those of Example 1. The specific steps were as follows:

[0059] S1. 10 parts by mass of 2-hydroxy-3-phenoxypropyl propyl acrylate and 1 part by mass of sodium methacrylate were scraped and mixed in a container to obtain a premix;

[0060] S2. 25 parts by mass of bisphenol F diglycidyl ether, 9 parts by mass of m-phenylenediamine, 0.5 parts by mass of γ-glycidoxypropyl trimethoxysiloxane, 0.5 parts by mass of carbon black and the premix were scraped and mixed in a container, followed by adding 50 parts by mass of silica and continuing to scrape and mix evenly after passing three rollers twice to obtain a mixture;

[0061] S3. The mixture was transferred to a dual planetary hybrid stirring kettle and stirred for 30 minutes. The wall was scraped when the stirring time was 15 minutes. The obtained product was then vacuumed and degassed and then discharged to obtain an epoxy adhesive.

[0062] Comparative Example 3

[0063] A reference epoxy adhesive was prepared according to the method of Example 1, except that 2-hydroxy-3-phenoxypropyl acrylate was replaced by propylene carbonate in the same weight portion, and the other conditions were the same as in Example 1 to obtain an epoxy adhesive.

[0064] Test Case

[0065] The epoxy adhesives obtained in the above examples and comparative examples were tested for bonding performance, heat resistance, and high temperature and high humidity resistance before and after power-on according to the following methods. The results are shown in Table 1.

[0066] (1) Bonding strength test before power on: Use a glue dispenser to dispense the epoxy adhesive obtained in the embodiment and the comparative example at 110°C, apply a 25mm*4mm rectangular glue line on the stainless steel substrate, and then bond another stainless steel substrate to the stainless steel substrate. After bonding, cure the sample in an environment of 165°C for 2h to obtain the sample to be tested. Use a universal material testing machine to run the sample to be tested along the shear direction at a speed of 10mm / min until the sample fails to bond, record the maximum force value displayed by the instrument, and calculate the shear bonding strength of the adhesive to the stainless steel substrate in combination with the bonding area.

[0067] (2) Bonding strength after power-on: After the glue is dispensed and cured according to the method in (1), the sample to be tested is obtained. The positive and negative wires of the DC power supply are clamped at the two ends of the sample respectively. The power is applied at a voltage of 48 V or 60 V for 30 min or 20 min. After the power-on is completed, the sample is removed and the sample to be tested is run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample fails to bond. The maximum force value displayed by the instrument is recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after power-on is calculated based on the bonding area (when the bonding strength is less than 2 MPa, it is removable).

[0068] (3) Heat resistance (80°C): After curing the adhesive according to the method in (1), the sample to be tested was obtained. The bonded sample was placed in an oven at 80°C for 20 min. Then, a universal material testing machine was used to run the prepared bonding sample in an environment of 80°C at a speed of 10 mm / min along the shear direction until the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80°C was calculated based on the bonding area.

[0069] (4) High temperature and high humidity resistance (85°C, 85% RH): The test sample was obtained after curing by the method in (1). The bonded shear sample was placed in a high temperature and high humidity oven at 85°C and 85% RH for 7 days. The prepared bonding sample was run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample failed to bond. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging was calculated based on the bonding area.

[0070] Table 1

[0071]

[0072] It can be seen from the results in Table 1 that the epoxy adhesive provided by the present invention has a high bonding strength, which can reach more than 10 MPa, and can meet the conventional use requirements. At the same time, the bonding strength can be reduced to less than 2 MPa after power is applied, that is, it has good detachability.

[0073] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that when no alkali metal salt is added or the amount of alkali metal salt is lower than the scope of the present invention, although a relatively high bonding strength can still be maintained, the bonding strength remains at a relatively high level after power is applied and cannot be reduced to below 2 MPa, that is, it does not have detachable properties.

[0074] From the comparison between Example 1 and Comparative Example 3, it can be seen that when the solid electrolyte is selected as polyethylene oxide PEO solid electrolyte, not only the bonding strength will be reduced, but also the bonding strength cannot be reduced to below 2 MPa after power is applied, that is, it does not have detachable properties.

[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. An epoxy adhesive, characterized in that: The epoxy adhesive contains epoxy resin, epoxy acrylate resin, alkali metal salt and optional curing agent, coupling agent, color powder, inorganic filler and auxiliary agent. The mass ratio of the epoxy resin, epoxy acrylate resin and alkali metal salt is 100:(20-150):(20-200).

2. The epoxy adhesive according to claim 1, characterized in that The content of the epoxy resin is 10 to 25 parts by weight, the content of the epoxy acrylate resin is 5 to 15 parts by weight, the content of the alkali metal salt is 5 to 20 parts by weight, the content of the curing agent is 5 to 20 parts by weight, the content of the coupling agent is 0.1 to 5 parts by weight, the content of the color powder is 0.1 to 5 parts by weight, the content of the inorganic filler is 30 to 60 parts by weight, and the content of the auxiliary agent is 0 to 20 parts by weight.

3. The epoxy adhesive according to claim 1, characterized in that: The epoxy resin is an aromatic epoxy resin and / or an aliphatic epoxy resin, preferably at least one selected from bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, o-hydroxymethyl bisphenol A diglycidyl ether, dihydroxymethyl bisphenol A diglycidyl ether, tetrabromobisphenol A diglycidyl ether, resorcinol diglycidyl ether, pyrogallol triglycidyl ether and pentaerythritol diglycidyl ether, more preferably bisphenol A diglycidyl ether and / or bisphenol F diglycidyl ether.

4. The epoxy adhesive according to claim 1, characterized in that: The viscosity of the epoxy acrylate resin at 25° C. is 500 to 20,000 mPa.s. Preferably, the epoxy acrylate resin is in liquid state at room temperature.

5. The epoxy adhesive according to claim 1, characterized in that: The epoxy acrylate resin is selected from at least one of 2-hydroxy-3-phenoxypropyl acrylate, bisphenol A epoxy acrylate, fatty acid epoxy acrylate, novolac epoxy acrylate, epoxy soybean oil acrylate and epoxy diacrylate.

6. The epoxy adhesive according to claim 1, characterized in that: The alkali metal salt is a compound composed of an alkali metal cation and at least one anion selected from the group consisting of an organic acid anion, an inorganic acid anion, and an organic sulfonyl imide anion.

7. The epoxy adhesive according to claim 6, characterized in that: The alkali metal salt is selected from at least one of sodium acrylate, potassium acrylate, sodium methacrylate, potassium methacrylate, lithium chloride, sodium chloride, potassium chloride, lithium acetate, sodium acetate, potassium acetate, lithium carbonate, sodium carbonate, potassium carbonate, lithium sulfate, sodium sulfate, potassium sulfate, lithium nitrate, sodium nitrate, potassium nitrate, lithium tetrafluoroborate, sodium tetrafluoroborate, potassium tetrafluoroborate, lithium hexafluorophosphate, sodium hexafluorophosphate, potassium hexafluorophosphate, lithium hexafluoroantimonate, sodium hexafluoroantimonate, potassium hexafluoroantimonate, lithium trifluoromethanesulfonate, sodium trifluoromethanesulfonate, potassium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonimide, sodium bistrifluoromethanesulfonimide, and potassium bistrifluoromethanesulfonimide.

8. The epoxy adhesive according to claim 1, characterized in that: The curing agent is selected from at least one of an amine curing agent, an acid anhydride curing agent and an imidazole curing agent; Preferably, the coupling agent is selected from at least one of γ-aminopropyl triethylsiloxane, γ-glycidoxypropyl trimethoxysiloxane, γ-methacrylate propyl trimethoxysiloxane, γ-mercaptopropyl trimethoxysiloxane, vinyl tri-tert-butyl peroxide silane, β-hydroxyethyl-γ-aminopropyl triethoxysiloxane, aniline methyl triethoxysilane and diethylene triaminopropyl triethoxysilane; Preferably, the toner is selected from at least one of carbon black, iron oxide toner, chromate toner, cadmium toner, ultramarine and phthalocyanine blue; Preferably, the inorganic filler is selected from at least one of calcium carbonate, dolomite powder, calcite, quartz powder, kaolin powder, calcined kaolin powder, talc powder, mica powder, feldspar powder, wollastonite powder, silica powder, sepiolite powder and glass powder; Preferably, the auxiliary agent is selected from at least one of a defoamer, a leveling agent, a dispersant and an antioxidant.

9. The method for preparing the epoxy adhesive according to any one of claims 1 to 8, characterized in that: The method comprises the steps of uniformly mixing epoxy resin, epoxy acrylate resin, alkali metal salt, and optional curing agent, coupling agent, color powder, inorganic filler and auxiliary agent to obtain epoxy adhesive.

10. Use of the epoxy adhesive according to any one of claims 1 to 8 in bonding electronic products.